2015
DOI: 10.1111/his.12741
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic adult‐onset leucodystrophy with axonal spheroids and pigmented glia with no mutations in the known targeted genes

Abstract: We add support to the idea that all these entities are closely related diseases linked to a convergent metabolic pathway, but caused by different genes or perhaps by the combination of individually non-pathogenic variations of selected genes. Genetic defects are still barely known in a substantial number of adult leucodystrophies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…There have been several cases in which clinical and pathologic findings were consistent with ALSP, but CSF1R mutations were not identified. [17][18][19] Notably, no CSF1R mutation has been found in the original Swedish family, 20 implying that other genes may be associated with these cases. In 2016, homozygous or compound heterozygous mutations in AARS2 gene encoding mitochondrial alanyl-transfer RNA synthetase were identified in 5 patients who were clinically suspected to have ALSP, but were negative for CSF1R mutations.…”
Section: Historical Background and Nosologymentioning
confidence: 95%
“…There have been several cases in which clinical and pathologic findings were consistent with ALSP, but CSF1R mutations were not identified. [17][18][19] Notably, no CSF1R mutation has been found in the original Swedish family, 20 implying that other genes may be associated with these cases. In 2016, homozygous or compound heterozygous mutations in AARS2 gene encoding mitochondrial alanyl-transfer RNA synthetase were identified in 5 patients who were clinically suspected to have ALSP, but were negative for CSF1R mutations.…”
Section: Historical Background and Nosologymentioning
confidence: 95%
“…However, there is also evidence that TREM2 can associate with other receptors, including PlexinA1 [ 273 , 274 ]. Other studies are suggestive that TREM2 could also bind to TREML1 [ 236 ] through co-IP experiments or CSF1R due to their close linkage in network analyses [ 101 ] and the strong commonalities in their downstream pathways [ 222 , 275 ]. While these last two interactions remain to be validated, it is certainly possible that TREM2 also acts through these alternative heteromeric complexes.…”
Section: Trem2 Structure and Signalingmentioning
confidence: 99%
“…The formation of axonal spheroid is considered as a pathological manifestation of CSF1R-related leukoencephalopathy. 71,72 Tada et al indicated that in layers 3 and 4 of the frontal cortex in CSF1Rrelated leukoencephalopathy fewer numbers of Iba1 positive microglia were recorded than healthy control brains. A high proliferation of microglia was noted in selective brain regions.…”
Section: Dovepressmentioning
confidence: 99%